VC2 and V1/2Mn1/2C2 nanosheets with robust mechanical and thermal properties as promising materials for Li-ion batteries. Issue 3 (8th January 2019) - Zhang, Bingwen; Zhang, Weiyi; Meng, Qiangqiang; Fan, Lele; Zhang, Qinfang
Abstract : In this paper, vanadium carbides VC2 and bi-transition-metal carbides V1/2 Mn1/2 C2 are predicted to be stable metallic nanosheets showing promising mechanical properties. Abstract : In this paper, vanadium carbides VC2 and bi-transition-metal carbides V1/2 Mn1/2 C2 are predicted to be stable metallic nanosheets showing promising mechanical properties and their Young's moduli are 70.8 N m −1 and 83.7 N m −1, respectively. Ab initio molecular dynamics results showed that both VC2 and V1/2 Mn1/2 C2 can tolerate temperatures up to 1000 K showing favorable thermal properties. The excellent Li-ion specific energy storage capacity and low diffusion barrier also make them promising candidates as anode materials. In addition, nonmagnetic–ferromagnetic (–ferrimagnetic) transitions in VC2 and V1/2 Mn1/2 C2 can be tuned easily by oxygen or fluorine passivation.